1987
DOI: 10.1007/bf01296293
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms in endoluminal release of serotonin and substance P from feline jejunum

Abstract: The mechanisms controlling vagally induced 5-HT and SP release into the jejunal lumen were studied in the cat. In control animals, electrical vagal nerve stimulation doubled the rate of endoluminal secretion of 5-HT and SP. Propranolol pretreatment did not alter luminal secretion of these hormones. Atropine suppressed motor function and induced dose-related inhibition of vagal release of endoluminal 5-HT, but not of SP; the response to hexamethonium pretreatment was similar to that of atropine. In contrast, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…EC cells have been considered to release 5-HT mainly into the blood vessels and/or intrinsic nerve terminal via a basolateral border (21). In contrast, others showed that 5-HT is also released into the intestinal lumen (1,15,28,35). We have recently demonstrated that 5-HT is released into the lumen, but not into the portal circulation in response to luminal pressure increase of the rat proximal colon (55).…”
Section: -Ht3 Receptors; 5-ht4 Receptors; Enterochromaffin Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…EC cells have been considered to release 5-HT mainly into the blood vessels and/or intrinsic nerve terminal via a basolateral border (21). In contrast, others showed that 5-HT is also released into the intestinal lumen (1,15,28,35). We have recently demonstrated that 5-HT is released into the lumen, but not into the portal circulation in response to luminal pressure increase of the rat proximal colon (55).…”
Section: -Ht3 Receptors; 5-ht4 Receptors; Enterochromaffin Cellsmentioning
confidence: 96%
“…EC cells release 5-HT into the blood vessels and intrinsic nerve terminal via a basolateral border (21). 5-HT is also released into the intestinal lumen from EC cells (1,15,28,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of in vivo studies have shown a measurable amount of serotonin (5HT) in the intestinal lumen of various species. Known stimulants for such luminal release of 5HT include vagal nerve stimulation (Ahlman et al 1981;Grönstad et al 1987;Zinner et al 1982), luminal acidification (Kellum et al 1983;Resnick and Gray 1962), food intake (Ferrara et al 1987) or an increase in luminal pressure (Bülbring and Crema 1959). Luminal release of 5HT has also been examined in vitro using isolated mucosa/submucosal sheets, and known stimulants include mucosal acidification and cholinergic and β-adrenergic mechanisms Miller 1982, 1983;Kellum et al 1983Kellum et al , 1984a.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others showed that 5-HT is also released into the intestinal lumen in response to vagal nerve stimulation (1,20), luminal acidification (25), and food intake (10). Immunoelectron microscopic study showed the anatomical evidence that 5-HT is released from EC cells in response to an increase of luminal pressure of the rat duodenum (12).…”
mentioning
confidence: 99%